Use of Thyroid Hormones in Hypothyroid and Euthyroid Patients: A 2020 THESIS Questionnaire Survey of Members of the Swedish Endocrine Society - Planck, Tereza; Lantz, Mikael; Perros, Petros; Papini, Enrico; Attanasio, Roberto; Nagy, Endre V.; Hegedüs, Laszlo (Frontiers in Endocrinology, 2021)
Background: The standard treatment of hypothyroidism is levothyroxine (LT-4). However, there are several controversies regarding treatment of hypothyroid patients. Aim: To investigate the Swedish endocrinologists’ use of thyroid hormones in hypothyroid and euthyroid individuals. Methods: Physician members of the Swedish Endocrine Society (SEF) were invited by e-mail to participate in an online survey investigating this topic. Results: Out of the eligible 411 members, 116 (28.2%) responded. The majority (98.9%) stated that L-T4 is the treatment of choice. However, around 50% also prescribed liothyronine (L-T3) or a combination of L-T4+L-T3 in their practice. Combination therapy was mostly (78.5%) used in patients with persistent hypothyroid symptoms despite biochemical euthyroidism on L-T4 treatment. Most respondents prescribed L-T4 tablets and did not expect any major changes with alternative formulations such as soft-gel capsules or liquid formulations in situations influencing the bioavailability of L-T4. In euthyroid patients, 49.5% replied that treatment with thyroid hormones was never indicated, while 47.3% would consider L-T4 for euthyroid infertile women with high thyroid peroxidase (TPO) antibody levels. Conclusion: The treatment of choice for hypothyroidism in Sweden is L-T4 tablets. Combination therapy with L-T4+L-T3 tablets was considered for patients with persistent symptoms despite biochemical euthyroidism. Soft-gel capsules and liquid solutions of L-T4 were infrequently prescribed. Swedish endocrinologists’ deviation from endocrine society guidelines merits further study.